PEMODELAN NUMERIK HIDRODINAMIKA DAN ANGKUTAN SEDIMEN 1 DIMENSI PADA SALURAN BERCABANG - Kurniati, Teti
Abstract : The 1-D hydrodinamic equatiuons on branching channel were solved by using finite diffrence numerical with Abbott Ioneschu scheme. The test result on some cases of branching chennel show that the model produced satisfactory result. The convection-diffusion equation governig sediment transport was solved by using splitting technique proposed by Abarbanel and Gotttlieb. In this technique the transport equation was splitt into three different process equation, pure convection, pure diffusion and pure reaction equations. The pure convection equation was solved by using Ultimate Quickest sheme, the pure diffusion was solved by using central scheme while the pure reaction equation was solved by using Euler scheme.